Hubungan riwayat sarapan pagi, tingkat kecukupan gizi makro dan status gizi dengan prestasi belajar anak di SD Inpres Lili Kabupaten Kupang - Natalia, Kaho Devi; Picauly, Intje; Sinaga, Mindo (Institute for Advanced Science, Social, and Sustainable Future, 2023)
Breakfast is a very important mealtime, representing 15-25% of the total daily energy intake or 15-30% of the total daily nutrient intake to achieve a healthy, active, and intelligent life. Nutritional status has a significant influence on the level of intelligence and understanding of lessons in the classroom; if a child's nutritional status is insufficient or even poor, it affects the incompleteness of subject understanding and weakens learning outcomes. The purpose of this research is to analyze the history of breakfast, adequacy of macronutrients, and nutritional status with the academic achievement of children at Inpres Lili Elementary School, Kupang Regency. This type of research is an analytical observational study using a cross-sectional approach. The research sample was determined using purposive sampling method, which consisted of 137 students from Inpres Lili Elementary School, Kupang Regency. Statistical tests used were Chi-Square test and multiple logistic regression. Bivariate analysis results show a significant relationship between breakfast (p=0.000), level of macronutrient adequacy (p=0.000), and nutritional status (p=0.000) with academic achievement. Multivariate analysis results show that the history of breakfast, adequacy of macronutrients, and nutritional status are significantly related to academic achievement. Therefore, schools should implement routine nutritional and health monitoring programs and provide counseling or training on balanced nutritious food consumption.